Der Transmissionsmechanismus der Geldpolitik: Warum springt die Kreditvergabe nicht an? - Daniel Hagemann; Monika Wohlmann (Wirtschaftsdienst, 2017)
Seit dem Ausbruch der Finanzkrise hat die Europäische Zentralbank (EZB) ihren Leitzins bis auf 0% gesenkt, und über diverse Wertpapierankaufprogramme pumpt sie in bisher nie dagewesener Form Geld in die Märkte. Damit hat die EZB zwar ihr Ziel, das Zinsniveau an verschiedenen Märkten generell zu senken, erreicht, eine nennenswerte Belebung der Kreditvergabe der Geschäftsbanken an den privaten Sektor in der Eurozone ist jedoch bislang ausgeblieben. Warum aber springt die Kreditvergabe trotz der stark expansiven Geldpolitik nicht an? – – Despite heavily expansionary monetary policy, lending in the euro area has not increased noticeably in the last few years. This paper examines the banking lending channel as a transmission mechanism of monetary policy, and comes to the conclusion that banks have sufficient liquidity at their disposal, but mainly due to higher credit risks and tighter regulatory requirements do not use their liquidity for further lending. To make things worse, these obstacles have an even stronger effect in the peripheral countries, where lending needs to be boosted in particular, than in the core countries of the eurozone.
Keywords: E52; E44; G21; 330